Formononetin promotes porcine oocytes maturation and improves embryonic development by reducing oxidative stress - Na Wang; Han Yang; Yelei Chen; Hekun Wang; Chaorui Wang; Jianglin Fan; Yajie Chen; Yinghua Li; Maobi Zhu (Frontiers in Cell and Developmental Biology)
Increasing evidence has demonstrated that oxidative stress impairs oocyte maturation and embryonic development. Conventionally, antioxidants have been applied in vitro systems to improve oocyte maturation and blastocyst rates. Formononetin (FMN) is a flavonoid that has been shown to have various pharmacological effects, including antioxidants. In this study, we delved into the impact of FMN, acting as an antioxidant, on the in vitro development of oocytes and blastocysts within the culture system. FMN supplementation at 0.5 μM enhanced the rate of first polar body extrusion and blastocyst formation post parthenogenetic activation. It also increased mitochondrial function and ATP levels, reduced intracellular reactive oxygen species, and elevated intracellular GSH levels in both oocytes and embryos. Moreover, FMN significantly decreased autophagy and apoptosis levels in blastocyst cells, potentially via regulation of the Nrf2/Keap1 pathway. This is the first study to report that FMN supplementation benefits the in vitro culture of oocytes and early embryo development, potentially by regulating oxidative stress, mitochondrial function, and autophagy.